2015
DOI: 10.4172/2155-9600.s14-002
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Nutrients Diet Formulation of Broiler Poultry Rations in Nigeria Using Linear Programming

Abstract: The diet problem is a classic problem, one among the earliest problems formulated as a linear programming. The goal of the diet problem is to select a set of nutrients that will satisfy a set of daily nutritional requirement at minimum cost. Poultry being simple stomached species, cannot synthesize most of the nutrients required for them and so the nutrients become dietary essentials. Chicken has to be fed adequate quantities of balanced diet for its growth, livability and to exhibit its genetic potential to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 4 publications
1
9
0
1
Order By: Relevance
“…This indicates the proposed feed mix will reduce cost of finisher feed. Our results are in line with the findings of Oladokun and Johnson (2012) and Olugbenga et al (2015). Both the studies demonstrated that a reduction in cost of broiler feed could be achieved without compromising the nutrient content through the application of linear programming techniques.…”
Section: For Broiler Finishersupporting
confidence: 91%
See 2 more Smart Citations
“…This indicates the proposed feed mix will reduce cost of finisher feed. Our results are in line with the findings of Oladokun and Johnson (2012) and Olugbenga et al (2015). Both the studies demonstrated that a reduction in cost of broiler feed could be achieved without compromising the nutrient content through the application of linear programming techniques.…”
Section: For Broiler Finishersupporting
confidence: 91%
“…They were able to achieve a formulation that not only satisfied all requirements and constraints but also proffered a comparatively cheaper price than the existing formulation. Olugbenga et al (2015) carried out optimization of broiler feed rations at least cost with a case study of Nigerian poultries. A linear programming model was also applied for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Terdapat 24 fungsi konstrain dan 1 fungsi tujuan yang diselesaikan secara simultan dengan simpleks. Terdapat beberapa asumsi yang digunakan yakni linearity, simple objective, certainty, additivity, divisibility, non-negativity, finiteness dan proportionality (Olugbenga et al, 2015).…”
Section: Aditivitas : Setiap Fungsi Program Linierunclassified
“…While in Nigeria, the feed takes approximately 65-80% of all cost production [2]. Linear Programming (LP) is the commonly employed in optimizing diet formulation [3][4][5] and successfully reducing the cost. However, as a constraint in requirement more restricts and no violation is allowed, LP could not provide the feasible formula.…”
Section: Introductionmentioning
confidence: 99%